2019
DOI: 10.4103/jfmpc.jfmpc_339_18
|View full text |Cite
|
Sign up to set email alerts
|

Effect of iron and folic acid tablet versus capsule formulation on treatment compliance and iron status among pregnant women: A randomized controlled trial

Abstract: Background:Iron supplementation during pregnancy in programmatic settings has failed to produce desired results. Formulation of iron supplementation may have a role in compliance and hematological parameters.Objective:We did this study to compare the compliance to iron supplementation, change in mean hemoglobin and serum ferritin level after iron supplementation in capsule form and tablet form during pregnancy.Materials and Methods:In this single-blinded (investigator blinded), active comparator, randomized co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 12 publications
(13 reference statements)
0
3
0
1
Order By: Relevance
“…Daily iron requirements for the body can come from food sources or exogenous. Provision of iron from food can be increased through (1) Consumption of foods containing calories according to the needs of the body, (2) Increasing the availability of natural resources containing iron which can be used for food, disseminating information / promoting foods containing iron and avoiding types of foods that reduce the absorption process of iron in the body ( Yani, 2017;Srivastava et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Daily iron requirements for the body can come from food sources or exogenous. Provision of iron from food can be increased through (1) Consumption of foods containing calories according to the needs of the body, (2) Increasing the availability of natural resources containing iron which can be used for food, disseminating information / promoting foods containing iron and avoiding types of foods that reduce the absorption process of iron in the body ( Yani, 2017;Srivastava et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, efforts were made to supplement iron with a predetermined dose of one tablet a day, or the equivalent of 60 mg elemental iron and 0.25 mg folic acid. The tablets are consumed during 90 days of pregnancy (Habib et al, 2018;Srivastava et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, in this study we did Analysis of morphological parameters shows that folic acid may affect iron distribution and its utilization in rats; however, it appears that the obtained results also point to other mechanisms of folic acid effect on iron status. Several studies have indicated that simultaneous supplementation of folic acid and iron does not improve iron status [13][14][15]. Srivastava et al [13] found that 3-month supplementation with folic acid and iron did not significantly alter hemoglobin or ferritin concentration in women in the second trimester of pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of the prenatal women in the current study were between the ages of 25 and 30 years. However, Khorshid et al [ 13 ], Byamugisha et al [ 14 ], Ahamed et al [ 15 ], Kaundal et al [ 16 ], Sunuwar et al [ 12 ], Abujilban et al [ 17 ], Srivastava et al [ 18 ], Nahrisah et al [ 19 ], Bumrungpert et al [ 20 ], Sontakke et al [ 21 ], Mithra et al [ 22 ], Dutta et al [ 23 ], Kassa et al [ 24 ], and Boti et al [ 25 ] reported mean ages ranging from 22-30 years of age. Similar to a study done by Sontakke et al [ 21 ], pregnant women in the present study were equally divided according to their parity status as nulliparous and multiparous in intervention and non-interventional groups.…”
Section: Discussionmentioning
confidence: 99%